Enhanced dispersion of lignin in epoxy composites through hydration and mannich functionalization. Issue 1 (8th August 2014) - Mendis, Gamini P.; Hua, Inez; Youngblood, Jeffrey P.; Howarter, John A.
ABSTRACT Lignin was used as a biobased fill material to create epoxy composites. Lignin was incorporated into diglycidyl ether of bisphenol A–based epoxy using hydration and Mannich functionalization. The effects of chemical functionalization on the interfacial chemistry of lignin are examined, and the corresponding changes in materials properties are examined. Several types of lignin–epoxy composites were formed through dissolution of lignin in aliphatic amine. Lignin–amine solutions were modified through hydration and the Mannich reaction and were used to cure the epoxy. The resulting composites exhibited two‐phase microstructures containing lignin‐rich agglomerates. Thermomechanical properties were examined using dynamic mechanical analysis, differential scanning calorimetry, and fracture testing. Morphological and chemical changes were examined using scanning electron microscopy and Fourier transform infrared spectroscopy. The hydrated lignin samples showed similar glass transitions and mechanical properties to the neat epoxy samples. Interactions between water and the Mannich functionalized lignin decreased the glass transition temperature and mechanical properties of the highly hydrated Mannich reacted lignin samples because of a plasticization effect. Fracture testing was conducted on the samples and showed that the yield strength and elastic modulus were similar to the neat epoxy, but the fracture toughness decreased in the lignin‐containing specimen. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41263.